The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.18632/oncotarget.24931
|View full text |Cite
|
Sign up to set email alerts
|

CD200fc enhances anti-tumoral immune response and inhibits visceral metastasis of breast carcinoma

Abstract: CD200 is a widely expressed cell surface glycoprotein that inhibits excessive inflammation in autoimmunity, transplantation, and viral infections. We previously observed that visceral metastasis of highly aggressive and inflammatory 4THM breast carcinoma cells was markedly decreased in CD200 transgenic mice. The goal of this study was to determine whether exogenous exposure to CD200fc mimics the effects of endogenously over expressed CD200. Female BALB/c mice were injected with CD200fc two times a week for fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 51 publications
(68 reference statements)
0
10
0
Order By: Relevance
“…However, the CD200R-CD200 axis has also been reported as a co-stimulatory axis (Borriello et al, 1997;Wang et al, 2019). Furthermore, CD200R is required to 'license' TLR2mediated immune activation by Herpes Simplex Virus 1 in macrophages (Soberman et al, 2012), and the CD200R/CD200 axis in some cases was suggested to regulate protective antitumor responses (Erin et al, 2015;Erin et al, 2018;Liu et al, 2016). Taken together, although CD200R is generally considered to be an inhibitory receptor, there are data that suggest a more versatile and/or complex functionality of CD200R.…”
Section: Introductionmentioning
confidence: 99%
“…However, the CD200R-CD200 axis has also been reported as a co-stimulatory axis (Borriello et al, 1997;Wang et al, 2019). Furthermore, CD200R is required to 'license' TLR2mediated immune activation by Herpes Simplex Virus 1 in macrophages (Soberman et al, 2012), and the CD200R/CD200 axis in some cases was suggested to regulate protective antitumor responses (Erin et al, 2015;Erin et al, 2018;Liu et al, 2016). Taken together, although CD200R is generally considered to be an inhibitory receptor, there are data that suggest a more versatile and/or complex functionality of CD200R.…”
Section: Introductionmentioning
confidence: 99%
“…Collectively the associations between CD200R1 and these diverse immune-related proteins suggest that CD200R1 is involved in a variety of immune mechanisms and may explain why HNSCC with high CD200R1 expression is related to an 'immune-rich' microenvironment with high immune cell estimates. Thus, our findings suggest that modulation of the CD200R1 pathway could be used as an immunotherapeutic strategy in patients with HNSCC [22,35,36].…”
Section: Discussionmentioning
confidence: 71%
“…Several potential mechanisms have been associated with CD200R1 and immune responses [17,20,22]. For instance, 4THM breast cancer cell growth and invasion were increased in CR200R1KO mice and decreased in mice over-expressing CD200, with a lack of CD200R1 expression related to decreased CD8 + and CD3 + CD25 + T cells [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In preliminary studies, growth of tumor in this model was attenuated using therapy with anti-CD200mAb and was associated with augmented host anti-tumor immunity [ 94 ]. Interestingly, use of CD200fc, which is an CD200R1 agonist, significantly decreased the growth of metastatic breast cancer 4THM cells due to the inhibition of cancer-related inflammation and increase both the tumor-infiltrating CD8+ T cell number and tumor-induced IFN-γ secretion [ 95 ].…”
Section: Importance Of Cd200:cd200r Interactions In Transplantatiomentioning
confidence: 99%